Implementation of Novel Technique for Selective Harmonic Elimination in Multilevel Inverters Based on ICA. (17th June 2013) - Ajami, Ali; Oskuee, Mohammad Reza Jannati; Mokhberdoran, Ata Ollah
Abstract : Eliminating the specific harmonics especially low-order harmonics of the output voltage of 9-level inverter using SHE-PWM control scheme is investigated. Harmonic minimization is the intricate optimization problems because the nonlinear transcendental equations have multiple local optima. Increasing the degrees of freedom in the suggested method means that the number of switching angles increases. The suggested method is able to eliminate high number of undesired harmonics. As the number of switching angles increases, using either traditional iterative techniques or resultant theory method gets useless. In this paper to overcome this problem the imperialist competitive algorithm (ICA) is used. Also a DC-DC converter is used to enhance the SHE performance in the range for which the conventional SHE methods do not have any solution. Experimental and simulation results of a 9-level inverter show that the proposed method effectively minimizes a large number of particular harmonics so the total harmonics distortion of output voltage will be lower.